XRCC1 and hOGG1 genes and risk of nasopharyngeal carcinoma in North African countries. - (:unkn) unknown (My University, 2011)
Although genetic susceptibility to nasopharyngeal carcinoma (NPC) has been recognized for a long time, little is known about the responsible genes. X-Ray repair cross-complementing protein 1 (XRCC1) and human 8-oxo-guanine glycosylase 1 (hOGG1) genes are involved in deoxyribonucleic acid (DNA) repair and were found associated with NPC risk in three Asian case-control studies. The objective of the present study was to test these genes in a sample from North Africa, one of the major NPC endemic regions in the world. Three single nucleotide polymorphisms (SNPs) in the XRCC1 gene and one SNP in the hOGG1 gene were genotyped in 598 NPC cases from Morocco, Algeria, and Tunisia and 545 controls frequency matched by recruitment center, age, sex, and urban/rural household. The genotype and allelic distributions for the hOGG1 (326)Ser/Cys SNP and for the XRCC1 (399)Arg/Trp, (280)Arg/His, and (194)Arg/Trp SNPs did not differ significantly among NPC cases and controls. The XRCC1 (194)Trp allele frequency was significantly lower in the North African population than in Asian population (f = 0.04 vs. 0.31 in Cantonese Chinese and 0.21 Han Chinese). The hOGG1 (326)Ser allele frequency was significantly higher in the North African population (f = 0.73) than in Asian populations (f = 0.39 in Taiwanese). The results of the present study obtained from a large sample indicate that the XRCC1 and hOGG1 genes are unlikely to play a role in the susceptibility to NPC in North Africans. Our results do not corroborate those found in Asian population on smaller samples.
Keywords: African Research